Long-term neurodevelopmental outcomes of infants born late preterm: a systematic review - Tripathi T; Dusing SC (Dove Medical Press, 2015)
Tanya Tripathi,1 Stacey C Dusing2,3 1Rehabilitation and Movement Science Program, Department of Physical Therapy, 2Department of Physical Therapy, 3Department of Pediatrics, Children's Hospital of Richmond, Virginia Commonwealth University, Richmond, VA, USA Purpose: Late preterm (LPT) births constitute a large proportion of the preterm births in the USA. Over the last few decades, there has been an increase in research focusing on the neurodevelopment of infants born LPT. The purpose of this research was to systematically review the long-term neurodevelopmental outcomes in LPT infants. Materials and methods: We identified studies by using PubMed, ERIC, CINAHL, and PsycINFO databases. The references of included papers were reviewed for additional papers that met the inclusion criteria. Included papers compared motor, cognitive, language development, or academic performance outcomes between individuals born LPT and a term control group assessed between 12 months and 18 years of age. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards for systematic reviews were utilized including a two-step, two-investigator review process. Results: Of the 4,720 studies found in the initial search, 20 studies met the inclusion criteria. Approximately 75% of the 16 studies that assessed cognitive outcomes reported cognitive delay in the LPT group when compared to their full-term counterparts. More than 50% of the seven studies that assessed motor outcomes suggested a delay in motor development in the LPT group in comparison to full-term. Fewer papers assessed academic performance and language in children born LPT; however, the majority identified borderline differences when LPT infants were compared to those born full-term. Conclusion: Evidence suggests that infants born LPT are at an increased risk of neurodevelopmental delay between 1 and 18 years of life when compared to those born at term. The delay is most evident in the cognitive domain of neurodevelopment. Children born LPT are also at a risk of delayed language development, motor development, and lower academic performance. The rate of developmental delay is reduced somewhat when controlling for social factors; however, group differences persist. Keywords: late preterm infants, developmental outcomes, motor development, cognitive development, language development and school performance